The Marl as a Natural Supply on Broiler Chicken Feed: Effects on the Starter Performance, the Abdominal Fat and the Dropping Moisture - Ouachem , D.; Kaboul, N. (International Journal of Poultry Science, 2012)
In a poultry farming context marked by strong economic and social pressures, many of substitute products to antibiotics were put on the market. Among these products, appear mainly, probiotics, essential oils, acidifiers, enzymes and others. Clay is a natural supply that could be used in poultry feed to achieve the same goals because it is a very abundant product in nature, inexpensive, widely used by hens raised outdoors. For this purpose, the incorporation of 3% of marl was tested on broiler chicken, at the young age and at 56 days. In this trial, the growth performances at 10 days, we again study (at 56 days) the state litter quality, the abdominal fat and the relative weight of the bursa of Fabricius. Results of starting period showed, on one hand, a significant increase of the weight gain of 16.2% (p = 0.001) and an improvement of the feed consumption ratio of 8.1% (p = 0.02) and on the other hand, at the finisher period, results showed that clay contribute significantly to increase dry matter of droppings (+18%; p = 0.02) and enhance the immunity by a higher relative weight of bursa of Fabricius (+24.3%; p = 0.01). Also, at slaughter, clay reduces significantly the abdominal fat by 5.08% (p = 0.04). Results of this trial confirm our previous observations and demonstrate the importance of the marl use in the diet of broiler chickens.